Contribution of Human Resource Management to the Business Performance of Entrepreneurs in Purwokerto - Fatmah Bagis; Akhmad Darmawan (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
This study aims to analyze the contribution of Human Resource Management to the Business Performance of Entrepreneurs. This research is a case study at the UKM association in Purwokerto and respondent from this study were 84 from UKM association. This study used data analysis techniques namely PLS (Partial Least Square) analyisis using Smart PLS 3.0. The results showed that recruitment and selection had effect on business performance, training and development had effect on business performance. The results also show that compensation has no significant effect on business performance. The results showed that performance appraisal has no significant effect on business performance. Basically the Human Resource Management function has a contribution to the business performance of SMEs. This is evidenced by the value of R2 49,2% of the variability in the construction of SME business performance is influenced by recruitment and selection factors, training and development, and performance appraisal. Keyword: Recruitment and selection, training and development, compensation, performance assessment, business performance